Successful reduction in rhino poaching in Nepal - Esmond Martin; Chryssee Martin; Lucy Vigne (Pachyderm)
Well deserving accolades, Nepal has succeeded in granting better protection for its Asian rhino population than has any other country. According to the 2011 census, Chitwan National Park, Bardia National Park and Suklaphanta Wildlife Reserve had a total of 534 greater one-horned rhinos. In that year, only one rhino was poached. In 2012, just one other rhino was illegally killed. In November 2010 the Nepalese government set up three wildlife crime-control committees to work together nationally and in the districts to combat poaching and illegal wildlife trade in coordination with the Department of National Parks and Wildlife Conservation, the Forest Department, Customs, the army, the police, the National Investigation Department and the Crime Investigation Bureau. Emphasis was placed on apprehending traders, identifying smuggling routes and enlisting other governments in the region to coordinate action against wildlife culprits. The cooperation of Nepal’s own government departments, help from non-government conservation organizations and commitment from local people living near the boundaries of the three protected wildlife areas led to more measures taken to ensure rhino protection. These measures included training of law-enforcement officers, enforced severe penalties for wildlife crimes, better anti-poaching units composed of members of the communities living around the parks, improved intelligence gathering, and more money allocated to the communities as a result of increased park income from higher entry fees, and a higher number of tourists. Local communities receive 50% of the gross income of the three protected areas. In addition, local communities are financially benefiting from providing more amenities to tourists. Despite escalating prices for rhino horn in China and Vietnam, Nepal has curtailed poachers and traders. Other rhino range States in Asia and Africa have much to learn from Nepal’s successes in rhino protection.